Providing Water to the Plants Automatically Using Microcontroller - Mengistie, Dejenie (Edelweiss Applied Science and Technology, 2018)
In current situation, the field of agriculture farmers is facing major problems in watering their crops. Its because they are not aware of about the availability of the power. Even if it is available, they need to pump water and wait until the field is properly watered, which compels them to stop doing other activities which are also important for them, and thus they loss their precious time and efforts. But, there is a solution An Automatic Plant watering System not only helps farmers but also others for watering their gardens as well. The aim of the project is to use control engineering principles and concepts to provide a microcontroller based automatic plant watering system. The system will help in saving money and water and at the same time increasing crops production. The automatic plant watering system is controlled using ATmega328 micro controller based on arduino platform. The soil moisture/humidity levels are checked using soil moisture sensor. Whenever there is a change moisture/humidity in the soil the sensor senses change and gives signal to the micro-controller to activate or deactivate watering system.